The man and the state - Staver, Wesley Ohie (My University, 1894)
Introduction: “The worth of a state in the long run,” wrote John Stuart Mill, “is the worth of the individual composing it.” “We put too much faith in systems and look too little to new” was the opinion of Lord Beaconsfield; and a German writer of our own time holds it to be a very doubtful state of affairs, “when the man is sacrificed to the citizen.” In these several phrases are found questions that have for centuries been a battle ground for nations. Men have been slow to recognize and expound the fact of their great superiority over states. While few have been able to recognize our true sovereign, - the common man, many have been satisfied to accept the principle of state omnipotence and bend the knee to others who advocate its superiority over the man. This is only a form of superstition that has for years been advocated by a certain class, and today many have taken sides with this class, who seem to be willing to tear down our present system of government and establish a paternal policy instead, citing the prosperity of various European governments as arguments; to support their theory. Weak indeed, are these arguments, for in most European countries where the state is superior to man, great dissatisfaction prevails among the people, and government is often tyrannical and oppressive.
Citation: Staver, Wesley Ohie. The man and the state. Senior thesis, Kansas State Agricultural College, 1894.
Morse Department of Special Collections
Keywords: Government; Individualism; Citizen; Europe; State; Political science; Theses; Manuscripts (documents)